BIAS GENDER DALAM BERITA KRIMINALITAS PERKOSAAN: Analisis Tayangan Kriminalitas di Televisi - Rasito Rasito (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2020)
This writing is designed to analyze the impact of criminal-news of raping on television and it is analyzed based on gender perspectives. It is found that the given news events are bias as they feature women as weak, docile, taciturn, hopeless, powerless and careless and, in contrary, the men are featured as strong, powerful, smart, tricky, and full of sense. The truth-claim of conducting the rapes by the men are: uncontrolled emotion and of many external problems faced by the men. This crime-news should be formed appropriately to avoid gender bias and to avoid bad images on women as the victims of crimes. It is worsened by the fact, nowadays, that television is much more function as entertainment rather than as information-media.